Sanity of maize seeds comercialized in the 2006/07 growing season in Santa Catarina and Rio Grande do Sul States (Revista de Ciências Agroveterinárias, 2008)
Fungi are considered the main microorganisms associated and transmitted by maize seeds. They can decrease seed germination, seedling emergence and favor root and stalk rots. This study aimed to assess fungi occurrence and impact in maize seeds commercialized during the 2006/07 growing season in the States of Santa Catarina and Rio Grande do Sul. A total of 224 maize seed samples were analyzed (74 from Rio Grande do Sul and 150 from Santa Catarina). Samples were sent by producers, cooperatives and resale shops to the CAV / UDESC Phytopathology laboratory. From each sample, 100 seeds (four replications of twenty five seeds) were plated in the culture medium containing potato dextrose agar + antibiotic. A completely randomized block design was used. The material was incubated in growth chamber at 25 ºC and 12 hours of photoperiod during 10 days. The fungi incidence was based on the identification of pathogens colonies and / or structures. From the 224 samples analyzed, 70.5% were treated with fludioxonil+metalaxyl, 2.4% with fludioxonil+metalaxyl+benzimidazole, 10.4% with fludioxonil+metalaxyl+captan, 5.5% with fludioxonil+metalaxyl+carboxina +thiram, 9.8% with captan and 1.4% with thiram. The following fungi were identified: Fusarium verticillioides, Penicillium spp., Aspergillus flavus, Trichoderma spp., Cephalosporium sp., Fusarium spp., Rhizopus sp., A. Niger, Alternaria spp., Nigrospora sp., Stenocarpella maydis, Rhizoctonia sp., Bipolaris sp., Curvularia sp. Acremoniella sp., presenting, respectively, the following mean occurrence frequency values: 86.6%, 69.6%, 63.8%, 23.7%, 23.7%, 17.9%, 13.4% , 11.2%, 2.7%, 3.6%, 2.7%, 0.9%, 0.9%, 0.5% and 0.5%. F. verticillioides, Penicillium spp. and A. flavus showed the highest incidence with mean values of 14.0%, 12.4% and 8.4%, respectively. The results showed that seed treatment with fungicide performed by seed companies did not eradicate fungi that cause seed decay and stalk rot.
Keywords: Zea mays; chemical control; fungi; seed treatment.